2020
DOI: 10.3390/ani11010007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Methionine Deficiency Followed by a Re-Feeding Phase on the Hepatic Antioxidant Activities of Lambs

Abstract: Our objective was to investigate the effect of methionine restriction and resuming supply on liver antioxidant response in lambs. The concentrations of methionine and its metabolites and the expression of the nuclear factor erythroid 2-related factor 2 (Nrf2), a redox sensitive factor, were detected after methionine restriction treatment for 50 days and methionine supply recovery for 29 days. The expression of glutathione (GSH) S-transferase (GST), superoxide dismutase (SOD), catalase (CAT), and glutathione pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…Additionally, the current study observed that with the reduced supplemental Met to Cys ratios, the serum TAC and the liver GSH concentration linearly decreased. These results corresponded with previous studies showing that Met is essential in maintaining the antioxidant status of the animals ( Atmaca, 2004 ; Wu et al, 2017 ; Séité et al, 2018 ; Liu et al, 2020 ). Nevertheless, the current study further suggested that Met might hold greater significance than Cys in preserving the antioxidant capacity of the birds through mechanisms beyond serving as the GSH precursors since increasing Cys supplementation did not offset the decline in antioxidant capacity.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the current study observed that with the reduced supplemental Met to Cys ratios, the serum TAC and the liver GSH concentration linearly decreased. These results corresponded with previous studies showing that Met is essential in maintaining the antioxidant status of the animals ( Atmaca, 2004 ; Wu et al, 2017 ; Séité et al, 2018 ; Liu et al, 2020 ). Nevertheless, the current study further suggested that Met might hold greater significance than Cys in preserving the antioxidant capacity of the birds through mechanisms beyond serving as the GSH precursors since increasing Cys supplementation did not offset the decline in antioxidant capacity.…”
Section: Discussionsupporting
confidence: 92%
“…This notwithstanding, an entire line of research supports the hypothesis that lower methionine intake reduces ROS generation and increases overall animal longevity. For instance, Liu et al [ 185 ] recently reported that dietary restriction of methionine in lambs affects the redox system, changes the content of methionine and its metabolites in the liver and plasma, and, eventually, induces Nrf2 signaling pathway activation. This apparent discrepancy in the role of methionine on the regulation or redox balance is reconciled by the observation that reduced GSH levels, consequent to methionine restriction, induce the activation of the antioxidant response through Nrf2 as a compensatory mechanism.…”
Section: Nrf2-activating Natural Organosulfur Compoundsmentioning
confidence: 99%